Pengaruh Dukungan Sosial terhadap Adaptasi Pelayanan Kesehatan pada Tenaga Kesehatan Selama Pandemi Covid-19 - Glorya Riana Latuperissa; Budi Utomo; Makhfudli Makhfudli (FORIKES, 2022)
Introduction: The increase in the number of patients exposed to Covid-19 during the pandemic period raises great concern and psychological pressure including depression, anxiety, and stress on health workers so that this can affect health services to adapt. This study aims to assess the effect of social support on the adaptation of health services to health workers during the Covid-19 pandemic. Method: The study was a systematic review with The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach. It was need an article searched in Scopus, Science Direct, Spinger Link, ProQuest, and EBSCO database and classifying them into four points: social support, psikologis, adaptation, and health services. Inclusion criteria in the study literature were documents type was an original articl, the source from journals, article in English, and available in full text. The publication time limit was 2016 to 2021. We identified 11 articles deemed relevant. Results: Health workers had high levels of anxiety during the covid-19 pandemic. Social support has a positive psychological relationship with health workers because it not only reduces negative symptoms but also creates positive coping mechanisms to promote adaptation in providing effective health services. Conclusion: Social support needs to be considered for health institutions to adopt a social support perspective in the implementation of daily health service adaptation. Further research is needed to determine the relationship between social support and adaptation to health services.Keywords: social support; health services; health personnel; health workforce; healthcare workers; adaptation; covid-19ABSTRAK Pendahuluan: Peningkatan jumlah pasien terpapar Covid-19 selama pandemi menimbulkan kekhawatiran dan tekanan psikologis yang besar termasuk depresi, kecemasan, dan stres pada tenaga kesehatan sehingga hal ini dapat mempengaruhi pelayanan kesehatan untuk beradaptasi. Penelitian ini bertujuan untuk mengkaji pengaruh dukungan sosial terhadap adaptasi pelayanan kesehatan pada tenaga kesehatan selama pandemi Covid-19. Metode: Penelitian ini merupakan penelitian sistematis dengan Tinjauan Sistematis dan Meta-Analisis (PRISMA). Database yang digunakan dalam pencarian artikel ini yaitu Scopus, Science Direct, Spinger Link, ProQuest, dan EBSCO dan mengklasifikasikannya ke dalam empat poin: dukungan sosial, psikologis, adaptasi, dan pelayanan kesehatan. Kriteria inklusi dalam studi literatur adalah artikel asli, sumber dari jurnal, artikel dalam bahasa Inggris, dan tersedia dalam teks lengkap. Batas waktu publikasi adalah 2016 hingga 2021. Kami mengidentifikasi 11 artikel yang dianggap relevan. Hasil: Tenaga kesehatan memiliki tingkat kecemasan yang tinggi selama masa pandemi covid-19. Dukungan sosial memiliki hubungan psikologis yang positif dengan petugas kesehatan karena tidak hanya mengurangi gejala negatif tetapi juga menciptakan mekanisme koping yang positif untuk mendorong adaptasi dalam memberikan pelayanan kesehatan yang efektif. Kesimpulan: Dukungan sosial perlu diperhatikan bagi institusi kesehatan untuk mengadopsi perspektif dukungan sosial dalam pelaksanaan adaptasi pelayanan kesehatan sehari-hari. Diperlukan penelitian lebih lanjut untuk mengetahui hubungan antara dukungan sosial dan adaptasi terhadap pelayanan kesehatan.Kata kunci: dukungan sosial; pelayanan kesehatan; tenaga kesehatan; tenaga kesehatan; tenaga kesehatan; adaptasi; covid-19